2005
DOI: 10.1086/430667
|View full text |Cite
|
Sign up to set email alerts
|

SINFONI in the Galactic Center: Young Stars and Infrared Flares in the Central Light‐Month

Abstract: We report 75 milli-arcsec resolution, near-IR imaging spectroscopy within the central 30 light days of the Galactic Center, taken with the new adaptive optics assisted, integral field spectrometer SINFONI on the ESO-VLT. To a limiting magnitude of K~16, 9 of 10 1 based on observations obtained at the Very Large Telescope (VLT) of the European Southern Observatory, Chile 1 stars in the central 0.4", and 13 of 17 stars out to 0.7" from the central black hole have spectral properties of B0-B9, main sequence stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
782
5
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 612 publications
(837 citation statements)
references
References 79 publications
45
782
5
5
Order By: Relevance
“…For observational purposes we also compute the apparent I magnitude for the candidates assuming M I = −4.6 (Battinelli & Demers 2005b). To determine the galactocentric distances for our candidates we adopt a distance between the Sun and the Galactic center R 0 = 7.62 ± 0.32 kpc (Eisenhauer et al 2005). This value was essentially confirmed by near infrared observations of red clump stars close to the Galactic Center (Nishiyama et al 2006).…”
Section: Distance Estimatesmentioning
confidence: 99%
“…For observational purposes we also compute the apparent I magnitude for the candidates assuming M I = −4.6 (Battinelli & Demers 2005b). To determine the galactocentric distances for our candidates we adopt a distance between the Sun and the Galactic center R 0 = 7.62 ± 0.32 kpc (Eisenhauer et al 2005). This value was essentially confirmed by near infrared observations of red clump stars close to the Galactic Center (Nishiyama et al 2006).…”
Section: Distance Estimatesmentioning
confidence: 99%
“…Schödel et al 2002;Ghez et al 2003;Eisenhauer et al 2005;Ghez et al 2005). In contrast to gas, the orbits of the stars are governed by gravitation only and therefore provide an excellent tracer for the gravitational potential in our Galactic center.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-wavelength detections of the radio point source at sub-millimeter, X-ray, and infrared wavelengths have also been made, showing that the luminosity associated with the black hole is many orders of magnitudes below that of active galactic nuclei (AGN) with comparable masses [5]. These observations have also shown that the emission from Sgr A* is variable [e.g., [6][7][8][9][10]. Although it is now easily detected in its bright states when its flux increases by up to an order of magnitude over time scales of 1 to 3 hours, Sgr A* is difficult to detect in its faintest states at X-ray wavelengths because of the strong diffuse background, and in the near-infrared because of confusion with nearby stellar sources [6,9].…”
Section: Introductionmentioning
confidence: 99%